Pulsatilla bohemica (Scalycky) Tzvelev ex situ та in situ - Козуб-Птиця, В.В. (Промышленная ботаника, 2010)
На основі результатів інтродукційного дослідження Pulsatilla bohemica (Scalycky) Tzvelev в Донецькому ботанічному саду виявлено особливості онтогенезу, сезонного розвитку рослин ex situ, показано ефективність розмноження свіжозібраним насінням та можливість плантаційного вирощування рослин в умовах розсадника з метою подальшої реінтродукції. Наведено результати дослідження стану популяцій рідкісного виду P. bohemica in situ на території південного сходу України. As a result of introduction research of Pulsatilla bohemica (Scalycky) Tzvelev in Donetsk Botanical Garden the peculiarities of ontogenesis, seasonal plant ex situ development have been determined, the efficiency of reproduction by fresh-gathered seed and the opportunity of plantation cultivation of plants under the conditions of seed plot with the purpose of further reintroduction have been shown. Research results of populations of rare P. bohemica in situ species on the territory of the Southeast of Ukraine have been given.